Clinical and Laboratory Findings That Differentiate Herpes Simplex Virus Central Nervous System Disease from Enteroviral Meningitis - Layli Sanaee; Monica Taljaard; Tim Karnauchow; Jeffrey J. Perry (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. It can be difficult for clinicians to distinguish between the relatively benign enteroviral (EnV) meningitis and potentially lethal herpes simplex virus (HSV) central nervous system (CNS) disease. Very limited evidence currently exists to guide them. Objective. This study sought to identify clinical features and cerebrospinal fluid (CSF) findings associated with HSV CNS disease. Methods. Given that PCR testing often is not immediately available, this chart review study sought to identify clinical and cerebrospinal fluid (CSF) findings associated with HSV meningitis over a 6-year period. In cases where PCR was not performed, HSV and EnV were assigned based on clinical criteria. Results. We enrolled 166 consecutive patients: 40 HSV and 126 EnV patients. HSV patients had a mean 40.4 versus 31.3 years for EnV, p=0.005, seizures 21.1% versus 1.6% for EnV, p<0.001, altered mental status 46.2% versus 3.2% for EnV, p<0.001, or neurological deficits 44.7% versus 3.9% for EnV, p<0.001. CSF neutrophils were lower in HSV (median 3.0% versus 9.5%, p=0.0002); median lymphocytes (87.0% versus 67.0%, p=0.0004) and protein (0.9 g/L versus 0.6 g/L, p=0.0005) were elevated. Conclusion. Our study found that HSV patients were older and more likely to have seizure, altered mental status, or neurological deficits than patients with benign EnV meningitis. HSV cases had lower CSF neutrophils, higher lymphocytes, and higher protein levels.